2020
DOI: 10.1177/0260106020971136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disordered eating behaviors and associated factors in Brazilian university students

Abstract: Background: University students may be a vulnerable group to adopt unhealthy behaviors, including changes in eating behavior. Assessment of factors associated with the prevalence of disordered eating behaviors in this population may facilitate the early identification of their predictors, thus allowing fast interventions. Aim: To analyze the prevalence of disordered eating behaviors (DEB) and associated factors in Brazilian university students. Methods: Cross-sectional study of male and female students aged 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
1
13
0
1
Order By: Relevance
“…Worldwide, there is moderate evidence of an association between overestimation of weight and unhealthy weight control strategies (use of diet medication, purging, or fasting) and disordered eating behaviors in children and adolescents [ 18 ]. In Brazil, a direct relationship was found between weight concerns and food restriction [ 19 ] or other eating disorders [ 20 ] in adolescents. Further, among Brazilian adolescents, the perceived weight, rather than actual nutritional status, tended to be more associated with extreme efforts toward weight control such as vomiting or laxative use [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, there is moderate evidence of an association between overestimation of weight and unhealthy weight control strategies (use of diet medication, purging, or fasting) and disordered eating behaviors in children and adolescents [ 18 ]. In Brazil, a direct relationship was found between weight concerns and food restriction [ 19 ] or other eating disorders [ 20 ] in adolescents. Further, among Brazilian adolescents, the perceived weight, rather than actual nutritional status, tended to be more associated with extreme efforts toward weight control such as vomiting or laxative use [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A insônia também pode estar associada a piores resultados no tratamento para transtornos alimentares, de modo que os profissionais de saúde devem considerar a incorporação de avaliações de saúde mental para insônia, depressão e ansiedade nos esforços atuais de prevenção, diagnóstico e intervenção dos transtornos alimentares 21,22 . Outro fator que tem sido relacionado às desordens no comportamento alimentar é a percepção elevada de estresse 23 . Similarmente, neste estudo, observou-se níveis elevados de estresse na maior parte dos pacientes com transtornos alimentares e verificou-se que esta alteração esteve associada ao menor número de residentes no domicílio do indivíduo.…”
Section: Resultsunclassified
“…In several studies, lifestyle factors such as smoking and alcohol use, physical inactivity, and unhealthy diet have also been associated with unhealthy eating behaviors [57,58]. In particular, an association was determined between smoking and food restriction behavior, and it was reported that smokers displayed food restriction behavior approximately twice as much as non-smokers [59]. It is also stated that most smokers tend to have lower body weights, and that smoking cessation often leads to overweight or obesity [60].…”
Section: Discussionmentioning
confidence: 99%